Ocular Manifestations in HIV Patients at Balung Regional Hospital, Jember - Mawardi, Reyhana Khansa; Wijayanti, Heni (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2022)
Introduction: Human Immunodeficiency Virus (HIV) infection predisposes individuals to various ocular complications, ranging from benign conditions like dry eye syndrome to severe, vision-threatening diseases such as CMV retinitis and HIV-associated retinopathy. These manifestations are significant markers of disease progression and correlate with viral load. Early identification and management of ocular conditions are crucial for preserving vision and improving the quality of life in HIV-positive patients. Aim: This study aimed to determine the ocular manifestations of HIV patients. Methods: This study was an observational study with a cross-sectional design and random sampling, involving a total of 20 samples, conducted in January 2024 at Eye Clinic at Balung Regional Hospital, Jember. Data were collected through history taking and ocular examinations, which included the variables of gender, age, antiretroviral (ARV) management, viral load, visus, and ocular manifestation. Data analysis was performed with statistical software. Results: A total of 20 samples were involved in this study. There were 8 women (40%) and 12 men (60%) with an average age of 41.7 years. The maximum duration of ARV treatment is 1-5 years. The viral load test showed that there were 13 respondents (65%) with suppressed viral loads. There were 16 respondents (80%) with visual acuity ≥ 6/12. Fundus examination showed that 8 respondents (40%) experienced ocular manifestations and 12 respondents (60%) did not experience ocular manifestations. The most frequent ocular manifestation identified was posterior uveitis (3 respondents). Conclusion: The most common ocular manifestation in HIV patients at Eye Clinic at Balung Regional Hospital, Jember was uveitis posterior. Routine screening is needed for HIV patients to assess the condition of the patient's eyes.